Unnecessary Roughness: Why the NCAA’s Heavy-Handed Amateurism Rules Violate the Sherman Antitrust Act - Stephen Shaver (Washington University Journal of Law & Policy, 2015)
The NCAA is facing liability for eligibility rules that violate the Sherman Antitrust Act. Student-athletes involved in this litigation allege that the NCAA illegally establishes zero as the price for which student-athletes sell their image and likeness to the organization, and additionally that the NCAA illegally refuses to deal with former college athletes regarding this matter. This Note examines the NCAA’s persistent defense in antitrust actions—that college athletes are amateurs as opposed to professionals—and argues that amateurism is not viable as a justification because college sports are not amateur, there exist less restrictive alternatives, and amateurism is not precompetitive as the NCAA claims.
Keywords: NCAA; likeness; Sherman antitrust act; student-athletes; unions